1976
DOI: 10.1104/pp.58.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Azolla-Anabaena azollae Relationship

Abstract: The water ferm, Azolla caroliniana Willd., containing the symbiotic, heterocystous blue-green alga, Anabaena azollae, has been studied uder various growth conditions to characterize its light-dependent production of H2. The response of H2 production to N2 and C2H2 and the absence of a differential effect of m-chlorocarbonyl cyanide phenylbydrazone on H2 production and C2H2 reduction, coupled with the paralel ihibition of both processes by DCMU imply that the production of H2 is nitrogenase-catalyzed and ATP-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…1) demonstrated that the maximum rate of C2H4 production occurred at 0.1 atm C2H2 in this association and, in accord with previous observations (11), 0.1 atm C2H2 inhibited H2 production by 95 to 97%. Although the inhibition of H2 production at any pC2H2 is somewhat greater than reported for in vitro studies (16), the pattern of inhibition is very similar.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1) demonstrated that the maximum rate of C2H4 production occurred at 0.1 atm C2H2 in this association and, in accord with previous observations (11), 0.1 atm C2H2 inhibited H2 production by 95 to 97%. Although the inhibition of H2 production at any pC2H2 is somewhat greater than reported for in vitro studies (16), the pattern of inhibition is very similar.…”
Section: Resultssupporting
confidence: 91%
“…In the intact association, the alga can provide the Azolla plant with its total nitrogen requirement. Previous studies showed that the symbiont contained nitrogenase and was capable of C2H2 reduction, ATP-dependent H2 evolution, and excretion of ammonia (10,11,13).Although C2H2 reduction is a simple and sensitive assay of nitrogenase activity, C2H2 is not the biologically important substrate, and the assay is an indirect measurement of nitrogen fixation. Since the reduction of N2 to 2NH3 requires six electrons while reduction of C2H2 to C2H4 requires two electrons, a theoretical conversion factor of 3C2H2 reduced per N2 fixed is frequently used in estimating nitrogen fixation from C2H2 reduction assays.…”
mentioning
confidence: 99%
See 3 more Smart Citations